Geographic concentration of companies and relationship resources at the horizontal level (2019)
Purpose – This paper analyzes how horizontal relationship resources collaborated in the value creation process of fruit producing and exporting companies geographically concentrated in the São Francisco River Valley (SFRV), Brazil. Design/methodology/approach – It is a qualitative case study, in which the units of analysis were the medium and large producing and exporting companies and the fruit cluster of the SFRV, understanding that both co-evolve. Semi-structured interviews were conducted with corporate, institutional, and support industry companies; there was also an analysis of secondary data using public and private documents. Content analysis was performed with the Atlas.ti software, which allowed a greater systematization of the findings. Findings – The results revealed particular patterns of collaboration that indicate conditions and contributions derived from the links established among firms within the cluster, highlighting companies’ strategies to create value. Significant volumes of demand, especially involving the international market, bring companies closer in terms of production protocols and joint business practices. These aspects favor collaboration in an essentially competitive environment. Participation in a cluster environment enhances cooperation ties by providing access to knowledge spillovers and, consequently, improving individual and collective competitiveness. Originality/value – The study provides advances in the knowledge in the area by considering the microeconomic level of the firm in the cluster, and it also expands the empirical evidence on organizational relationships by presenting a study of a Brazilian agricultural cluster.